Detailed characterisation of Si Gate-All-Around Nanowire MOSFETs at cryogenic temperatures. (May 2018) - Boudier, D.; Cretu, B.; Simoen, E.; Veloso, A.; Collaert, N.
Highlights: Gate-All-Around Nanowire MOSFETs are investigated from 50 K down to 4.2 K. Analog parameters are extracted in linear operation and saturation regimes. Transfer characteristics at very low drain voltage show subband scattering effects. Carriers quantum transport impacts noise power spectral densities. Low frequency noise spectrocopy is performed from 10 K to 70 K. Abstract: In this work, Gate-All-Around Nanowire MOSFETs have been studied at very low temperatures. DC behaviors have been investigated in the linear operation and saturation regions, giving access to several analog parameters. Static characteristics at 4.2 K and low polarization exhibit step- like variations of the drain current, which can be linked to energy subband scattering. First results on the impact of quantum transport mechanism on the low frequency noise are shown. Finally the low frequency noise spectroscopy has led to the identification of silicon film traps.